P13.13 Clinical factors involved in brain metastasis edema: results of a retrospective cohort and evaluation of the best edema descriptor. (6th September 2019) - Pin, Y; Loo, M; Waissi, W; Paix, A; Todeschi, J; Antoni, D; Proust, F; Ahle, G; Noël, G
Abstract: BACKGROUND: Brain metastasis (BM) are frequently surrounded by brain edema with a variable extension. This pathological increase in the water mass from the interstitial or intracellular space is the source of neurological symptoms but some studies also showed a prognosis impact of this edema. Nevertheless, the current edema evaluation methods are poorly reproducible and were not extensively evaluated. From a series of patients with brain metastasis, we analyzed factors influencing perilesional edema extension in function of three edema descriptors which were qualitatively evaluated: the absolute cumulative intracranial edema volume (CIEV, in mL), the edema on tumor volume ratio (ER), and the Edema Theoretical Thickness (ETT, in mm), new factor designed to be more independent from geometrical considerations. MATERIAL AND METHODS: Clinical, biological and imaging factors were retrospectively recorded from patients referred for upfront stereotactic radiotherapy of one to three BMs. CIEV, ER and ETT were calculated for each patient. Non-colinear factors were selected using the Farrar-Glauber test. Impact of these factors on edema was tested with an univariate then a multivariate linear regression for each edema descriptor. Each resulting regression model was qualitatively evaluated using the F-test, R square value and residuals calculation. RESULTS: Between January 2012 to December 2017, 182 patients were included. Upon 20 potentially prognostic factors recorded, 10 were kept, including clinical, biological and imaging factors. In the multivariate analysis, the CIEV was influenced by the cumulative intracranial tumor volume (CITV) (coefficient of 1.95, p<.001). The CIEV F-statistic p-value and R square were <10 –15 and 0.30, respectively. The ETT was significantly influenced by the CITV (0.31, p<.001) and the extracerebral disease control (-1.58, p=.049). The F-test p-value and R square were <10 -10 and 0.25, respectively. No significant linear regression was found for the ER. Residuals were more clinically relevant for the ETT compared to the CIEV. CONCLUSION: Being significantly influenced by the cumulative brain tumor volume and the extracerebral disease control, the ETT might be a factor to include in future BM works because its strong relationships with confounding factors and its ability to provide robust intra and inter subjects comparisons.